Can the duration of obesity, diet, and physical activity be determinants in metabolic healthy obesity? - Aritici Colak, Gozde; Saglam, Duygu (Progress in Nutrition, 2022)
Objective: A subgroup is defined as metabolic healthy obese, resistant to the development of complications caused by obesity. This study aims to evaluate the difference between obese subgroups in terms of diet, physical activity, and time spent obese. Methods: 401 individuals between the ages of 18-65 with a body mass index greater than 30 kg/m2 participated in the study. A questionnaire form was applied in which the general characteristics of the individuals were questioned, anthropometric measurements were made, and biochemical blood parameters were taken. Food consumption and physical activity records were taken. According to the metabolic syndrome diagnostic criteria, ATP III, individuals are classified as metabolically healthy or metabolically unhealthy. Results: At the end of the study, 60% of women (n=147) and 69% of men (n=109) were found to be metabolically unhealthy obese (p0.05). It was observed that the amount of energy, total fat, saturated fat, and carbohydrates taken with the daily diet are higher in those with unhealthy obesity than in the healthy obese (p0.05). The risk of metabolic unhealthy obesity was found to be 2.2 times higher in individuals with a body mass index over 30 kg/m2 for more than 10 years. After the age of 52, the risk of being obese with metabolic unhealthy is 2.5 times higher. Conclusion: It is thought that lifestyle may be a distinguishing factor in the group of obesity resistant to metabolic risk factors. Clarification of the possible effects of nutrition in metabolically healthy obese will be important in the treatment of obesity.